MEDIASI PERSPEKTIF HUKUM ISLAM (STUDI PERMA NO. 1 TAHUN 2008 TENTANG PROSEDUR MEDIASI DI PENGADILAN) - Imam Ali Bashori (Institut Agama Islam Negeri Metro, 2015)
Mediation is an alternative way to resolve disputes. With the approach of a win-win solution, mediation can bring a sense of fairness in resolving disputes without going through trial procedures are familiar with legal terminology that is difficult to understand by the general public. However, not all disputes can be resolved through mediation way. Perma No. 1 of 2008 on mediation procedure in court mediation limit applies only to disputes / civil cases. This paper questions the back of the scope and types of cases that can use alternative settlement by way of mediation. Here will be presented mediation according to the viewpoint of Islam well as analysis for Perma No. 1 Year 2008. Islamic law is an integral part of building laws in Indonesia, so that it opens the possibility of treasures in Islamic law becomes the input for the law in Indonesia, including on mediation. In the mediation of Islam known as Sulh encompass a broader scope than the scope of mediation in Perma No. 1 Year 2008. This paper will parse the opportunity to broaden the scope of mediation in Perma No. 1 of 2008 is based on the viewpoint of Islamic law, one of which is mediation in criminal cases. The State does not only present as a punisher, but more widely present state as a mediator in criminal matters (public).